Exploration of Religious Moderation with Local Culture among Samin Community, Bojonegoro - Setiawan, Nanang; Khamid, Abdul; Huda, Muhammad Miftakhul; Muntholip, Abd (UIN Maulana Malik Ibrahim Malang, 2023)
The promotion of religious moderation in Indonesia has become increasingly urgent amid the proliferation of radicalism and extremism among society. This research explores how religious moderation is realized in the daily lives of the Samin community in Bojonegoro. It is a qualitative study that involves observations of the community's traditional life and in-depth interviews with their leaders. The result unveils several local wisdoms: ngelmu iku sejatine dhewe (knowledge is truly one's own), ngudi ilmu (seeking knowledge), ponco soco (humble), ngluruk tanpa rupo (moving without a trace), nyawiji sepi ing pamrih (living in solitude without selfishness), nyawiji ngluruk (living without desire), ngganem sepi ing ngluruk (cultivating simplicity in living without expectations), and ngalembono (being serene). The local cultures play a substantial role in shaping and maintaining religious moderation. Customs and traditions are strong foundations for tolerance among religious communities, thereby creating harmony amidst the diversity of beliefs. This study contributes to a deeper understanding of the balance between religious moderation and local culture in that it provides new insights for researchers, practitioners, and readers interested in the field. It provides a positive contribution to support a better understanding of religious moderation in the local context, with a special focus on the unique experiences of the Samin community. Implementasi moderasi beragama di Indonesia sudah menjadi hal yang urgen di tengah banyaknya fenomena redikalisme dan ekstremisme di tengah masyarakat. Penelitian ini bertujuan untuk mengeksplorasi bagaimana moderasi beragama diwujudkan dalam kehidupan sehari-hari pada masyarakat Samin Bojonegoro. Penelitian ini bersifat kualitatif, melibatkan pengamatan kehidupan tradisional masyarakat Samin dan wawancara mendalam dengan tokoh masyarakat setempat. Hasil penelitian menunjukkan beberapa kearifan lokal di masyarakat Samin Bojonegoro, yaitu: ngelmu iku sejatine dhewe, ngudi ilmu, ponco soco, ngluruk tanpa rupo, nyawiji sepi ing pamrih, nyawiji ngluruk, ngganem sepi ing ngluruk, dan ngalembono. Budaya masyarakat Samin berperan penting dalam membentuk dan menjaga moderasi beragama. Adat dan tradisi menjadi pondasi yang kuat bagi terbentuknya toleransi antar umat beragama dan menciptakan kerukunan di tengah keberagaman keyakinan. Studi ini berkontribusi pada pemahaman yang lebih dalam tentang keseimbangan antara moderasi beragama dan budaya lokal sehingga memberikan wawasan baru bagi para peneliti, praktisi, dan pembaca yang tertarik dengan bidang ini. Diharapkan bahwa penelitian ini akan memberikan manfaat untuk mendukung pemahaman yang lebih baik tentang moderasi beragama dalam konteks lokal, dengan fokus khusus pada pengalaman unik masyarakat Samin.